Resources and dynamics of halophytes in agricultural and industrial landscapes of the western part of Kujawy, Central Poland - Karasińska, Wiesława; Nienartowicz, Andrzej; Kunz, Mieczysław; Kamiński, Dariusz; Piernik, Agnieszka (Ecological Questions, 2021)
This article is dedicated to the memoryof tireless researcher of saline vegetation in KujawyProfessor Jadwiga Wilkoń-Michalska (1921–2005) This paper presents the status and comparison of the halophytic flora on two research plots in the Upper Noteć catchment, distinguished by the intensity of human activity and the type of landscape: 1 – Lake Gopło (G) and 2 – the area located by the Noteć Canal (N) in the western part of the Kujawy region. Fishery on the twelfth largest lake in Poland and agriculture are the main forms of economy in the former plot. A significant part of this plot is a Natura 2000 site, legally protected in compliance with the EU directives. The development of halophytes, mainly facultative ones, in the G plot is conditioned by natural factors, i.e. the inflow of saline groundwater. In the N plot, the agricultural landscape was transformed into the industrial and urbanised landscape following the years of development of two soda factories and the municipal and housing infrastructure of the nearby town of Inowrocław. Strong human impact led to the fact that already several decades ago this plot was classified as one of the most ecologically endangered areas in Poland. The abundance of halophytes in the N plot, including many obligatory ones, is related to the geomorphology of the area and the associated pattern of salt deposit leaching, as well as brine exploitation and soda industry. The species composition and population resources of individual halophyte species at 65 sites on the G plot and 90 sites on the N plot were compared using numerical classification methods. The distribution of the sites and their species richness are presented on the maps of the study area. The results of our analysis were compared with the results of observations made by other authors in the same area at different times. Based on the comparative analysis, we have arrived at conclusions regarding the protection of halophytes and the anticipated effects of technological changes in agriculture, salt and soda industry, as well as spatial management. We believe that the data provided in the tables and the resulting maps will constitute reference points for assessing the effectiveness of undertaken conservation recommendations and the correctness of scenarios formulated by different authors for the development of natural systems in the study area.